Optimizations in Project Scheduling: A State-of-Art Survey - Wu, Changzhi; Wang, Xiangyu; Jiang, L. (Springer, 2014)
Abstract Project scheduling is concerned with an optimal allocation of resourcesto activities realized over time. To survive in today’s competitive environment, efficientscheduling for project development becomes more and more important. Theclassical project scheduling is based on the critical path method (CPM) in whichresources required are assumed unlimited. This is however impractical. To overcomeCPM’s drawback, several techniques and optimizations have been proposedin project scheduling literature. In this chapter, we will present a state-of-art surveyon project scheduling from the optimization point of view. In particularly, we willfocus on the advancements of optimization formulations and solutions on projectscheduling in the recent years.